2014
DOI: 10.1038/sc.2014.172
|View full text |Cite
|
Sign up to set email alerts
|

Locomotor training with body weight support in SCI: EMG improvement is more optimally expressed at a low testing speed

Abstract: Study design: Case series. Objectives: To determine the optimal testing speed at which the recovery of the EMG (electromyographic) activity should be assessed during and after body weight supported (BWS) locomotor training. Setting: Tertiary hospital, Sint Maartenskliniek, Nijmegen, The Netherlands. Methods: Four participants with incomplete chronic SCI were included for BWS locomotor training; one AIS-C and three AIS-D (according to the ASIA (American Spinal Injury Association) Impairment Scale or AIS). All w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…Amelioration in the locomotor patterns of incomplete SCI individuals following BWST includes an increase in EMG activity and a decrease in burst duration and cocontractions. 176,177 Gorassini and colleagues point out that the improvement in EMG activity is greater in muscles that receive more cortical projections (i.e., tibialis anterior [TA]and hamstrings), compared with muscles mainly under the influence of local spinal circuits (i.e., soleus). 176 It is argued that there may be a reinforcement of the remaining cortical and/or brainstem projections, a point that also is supported by the fact that the individuals more responsive to BWST were the ones with the highest remaining motor score for lower limb muscles.…”
Section: Greater Dependence Of the Locomotor Centers On Descending Symentioning
confidence: 99%
“…Amelioration in the locomotor patterns of incomplete SCI individuals following BWST includes an increase in EMG activity and a decrease in burst duration and cocontractions. 176,177 Gorassini and colleagues point out that the improvement in EMG activity is greater in muscles that receive more cortical projections (i.e., tibialis anterior [TA]and hamstrings), compared with muscles mainly under the influence of local spinal circuits (i.e., soleus). 176 It is argued that there may be a reinforcement of the remaining cortical and/or brainstem projections, a point that also is supported by the fact that the individuals more responsive to BWST were the ones with the highest remaining motor score for lower limb muscles.…”
Section: Greater Dependence Of the Locomotor Centers On Descending Symentioning
confidence: 99%
“…Body weight support systems coupled with robotic devices or pharmacologic treatments are now often used in the rehabilitation practice to assist locomotor recovery in individuals with neuromotor disorders (Dietz, 2009 ; Sale et al, 2012 ; Hubli and Dietz, 2013 ; Valentin-Gudiol et al, 2013 ; Meyns et al, 2014 ; Moraru and Onose, 2014 ). There is still limited evidence of the efficacy of treadmill interventions with body weight support in some injured populations due to the complex nature of the control of locomotion, compensatory strategies, and plasticity of neuronal networks (Grasso et al, 2004 ; Picelli et al, 2013 ; Valentin-Gudiol et al, 2013 ; Swinnen et al, 2014 ; Sylos-Labini et al, 2014b ).…”
Section: Introductionmentioning
confidence: 99%
“…29,30 Subsequently, there is evidence that in persons with MISCI, muscle activity is more optimal at lower speeds resembling self-selected speed. 31 In contrast, a recent study demonstrated that muscle activity increased as training intensity (that is, speed) increased. 32 However, walking was tested only on the treadmill, and therefore it is not known whether this translates to improvements in real-world overground walking.…”
Section: Dose-response Outcomes With Locomotor Training 1905mentioning
confidence: 91%